Can sharia supervisory board affect intellectual capital efficiency? - M. Arsyadi Ridha; Anis Chariri; Siti Mutmainah (Universitas Islam Negeri Walisongo Semarang, 2025)
Purpose - This study aims to examine the influence of Sharia Supervisory Board (SSB) characteristics on intellectual capital efficiency in Islamic banks in Indonesia. Method - This study employs a quantitative approach using panel data regression analysis. The population consists of Islamic banks in Indonesia, with the sample selected using a purposive sampling technique based on specific criteria. The final dataset comprises 63 observations from 10 Islamic banks over the period 2017–2023. Result - The findings reveal that SSB size, education level and meeting frequency do not significantly affect intellectual capital efficiency. However, SSB cross-membership positively influence intellectual capital efficiency. These results highlight the importance of external expertise and board activity in enhancing intellectual capital in Islamic banks. Implication - The study provides practical implications for regulators and Islamic bank managers in optimizing SSB governance structures to improve intellectual capital efficiency. Enhancing SSB effectiveness through cross-membership may contribute to better knowledge-sharing and decision-making processes, ultimately improving bank performance. Originality - To the best of our knowledge, there is still limited research that examines the direct impact of various SSB characteristics on intellectual capital efficiency in Islamic banks, particularly within the Indonesian context. This study therefore contributes to filling this gap in the literature by providing new evidence from an emerging Islamic banking market.